THE QUESTION OF THE CONSTITUTIONALITY OF RESTRICTIONS ON EMPLOYMENT IN THE PUBLIC SECTOR - Antić, Aleksandar (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Restriction of employment in the public sector implies a positively regulated absence of autonomy of employers in the public sector, when establishing a fixed-term and indefinite employment relationship, or when hiring a person to work outside the employment relationship. Employers in the public sector, except in exceptional situations, can establish employment for a definite and indefinite period of time, ie hiring persons outside the employment relationship, only after the consent of the Commission of the Government of the Republic of Serbia for giving consent for new employment and additional employment with users of public funds. The author analyze the constitutionality of the provisions that regulate the restriction of employment in the public sector. The question is whether the norms related to the regulation of employment restrictions in the public sector, are in conflict with the right to work, ie the prohibition of discrimination prescribed by the Constitution of the Republic of Serbia.